Obtaining of Boron as an Alternative Fuel from Borax with Various Methods - Şen, N.; Demir, C.; Demirbas, A.; Kar, Y. (Energy sources. Part A, Recovery, utilization, and environmental effects, 2009)
This study examined how to obtain elemental boron from borax. For this purpose, first boric acid (H 3 BO 3 ) was obtained from borax decahydrate with using HCl and H 2 SO 4 . The boric was then converted to boron oxide using a dehydration process. It has been studied to reduce the boric acid and the boron oxide into elemental boron with using the elemental magnesium (Mg) and butyl nitrite (C 5 H 9 NO 2 ), and also with using sawdust, charcoal, and cellulose. Then, the obtained elemental boron was subject to the burning process to prove its purity. The pure-elemental boron gave a strong green-colored flame when it was burned. Among these, the methods using the elemental magnesium (Mg) and butyl nitrite (C 5 H 9 NO 2 ) in order to obtain elemental boron are more reasonable than those of the others.